The Early Retirement Burden: Assessing the Costs of the Continued Prevalence of Early Retirement in OECD Countries - Tryggvi Thor Herbertsson; J. Michael Orszag (Institute for the Study of Labor (IZA), 2003)
Despite substantial increases in longevity, the age of retirement in the industrialized countries has steadily fallen throughout most of the 20th century. In France, for instance, the employment-population ratio of 55-64 year-old males fell from 74% in 1970 to 38.5% in 2000. In most other OECD countries, labor force participation rates for those 65 and above have fallen significantly. The economic cost of low labor market participation, in terms of lost output, benefit payments, and lower tax base is substantial. However, part of the cost of low labor market participation is cyclical or structural and hence separate from the costs of early retirement. This paper develops a simple framework to assess the specific costs of early retirement and applies it using data from the OECD countries. More significantly, we find that the costs associated with early retirement are projected to rise considerably in the next ten years from 7.6% of output in 2003 to 9.1% of output in 2010. This projected rise in the costs of early retirement over the course of the rest of the decade is slightly larger than the percentage point rise in the costs of early retirement over the twenty year period from 1982 to 2003. The projected rise in costs over the course of the next decade is largely due to population ageing, whereas the rise in costs over the past twenty years was primarily due to lower labor force participation of older workers.
Keywords: H55; J26; J21; J14; 330; early retirement; labor supply/demand; foregone output; Flexible Altersgrenze; Erwerbstätigkeit; Soziale Kosten; Wirtschaftswachstum; Schätzung; OECD-Staaten